Generation of Vertical Flows by Torsional Alfvén Pulses in Zero-beta Tubes with a Transitional Layer - Joseph Scalisi; Michael S. Ruderman; Robertus Erdélyi (The Astrophysical Journal, 2023)
Spicule activity in the chromosphere is modeled via the perturbation resulting from the propagation of an Alfvén wave pulse in a magnetic flux tube. Building on previous work, the model is augmented by the inclusion of a finite transitional layer in which the atmospheric density decreases exponentially. This additional complexity of the density stratification provides a more physical representation of the solar atmosphere and improves on the existing model. The wave pulse is introduced at the lower boundary of the flux tube and interacts with the transitional layer, also being partially reflected. The total mass flux induced by the pulse, and the proportion of this pulse that is transmitted through the layer, is calculated and examined in the context of spicules and the solar wind using an example solution. We find that the inclusion of the transitional layer results in more plasma flux being transferred into the upper solar atmosphere when compared with the case of a discontinuity. We examine how varying the parameters of this transitional layer affects the ratio of the flux above and below the layer.